In search of the causes of the globalization backlash: Methodological considerations on post-treatment bias - Paolo Agnolin; Italo Colantone; Piero Stanig (Fondazione Eni Enrico Mattei (FEEM), 2024)
We study the implications of post-treatment bias in the context of the globalization backlash. We discuss whether horse-race regressions can inform about the relative role of economic vs. cultural drivers. We make three methodological points: (1) if and insofar as cultural variables are post-treatment with respect to economic factors, the estimates of the effect of economic shocks on voting are biased in regressions that include cultural controls (and vice versa); (2) for the same reason, such horse-race regressions do not allow to accurately estimate the relative role of economic vs. cultural factors; (3) one cannot infer mediation effects from changes in regression coefficients for a given factor of interest before and after including post-treatment controls. We accompany the methodological discussion with empirical evidence on the relevance of post-treatment bias in studies of the globalization backlash, both by replicating and expanding on earlier studies, and by presenting novel cross-country results on the culture-economy nexus.
Keywords: F1; F5; 330; Globalization backlash; populism; radical right; post-treatment bias; causal mediation analysis